Nasal Cavity and Paranasal Sinus Cancer: Diagnosis and Treatment - Jakimovska, Frodita; Stojkovski, Igor; KJosevska, Elena (Springer Science and Business Media LLC, 2024)
The purpose of this review is to analyze the diagnosis and treatments of the sinonasal malignant tumors throw systematic reviewed literature. The systematic review of the literature was performed according to PRISMA guidelines.
Keywords: nasal cavity; Paranasal Sinus; cancer